Legal Protection for Land Rights Holders in Land Acquisition for Development in the Public Interest - Ali Sam'un; Tamaulina Sembiring; Ismaidar (Yayasan Multidimensi Kreatif, 2024)
Indonesia as a developing country needs infrastructure development in order to improve the welfare of the Indonesian people through this development. Every development activity carried out by the Government certainly cannot be separated from the need for land as a forum for its activities. The need for land has consequences for the use of land by land rights holders related to land acquisition for the implementation of development for the public interest. The increase in development activities has the consequence that more land is needed and later can cause problems in the land sector. The need for land that will be used by the government for development purposes must not harm the rights of land owners. Therefore, to regulate this, it is necessary to have a legal regulation that can provide legal protection to land rights holders. This research is descriptive analysis and normative law, namely describing all symptoms and facts and analyzing existing problems as well as research that uses secondary data sources or data obtained through legal literature materials. Judging from the approach, this research is the starting point of the problem by looking at the reality that occurs in the field and relating it to the applicable laws and regulations. This study uses a normative juridical approach, which is an approach by conducting an assessment and analysis of Legal Protection for Land Rights Holders in Land Acquisition for Development for the Public Interest.In order to provide maximum legal protection to land rights holders in the procurement of land for the public interest, the government should play an active role in its implementation to supervise parties who need land. The existence of the government in this case is very necessary so that in the implementation of land procurement carried out by agencies that need land is not done arbitrarily by taking rights to land owned by the community without providing fair and appropriate compensation.